EXAMINING THE EXTENT TO WHICH CANNABIS PROVISIONS HAVE BEEN INCORPORATED INTO NEW OR EXISTING CITY-LEVEL SOCIAL HOST ORDINANCES IN CALIFORNIA AND COLORADO - Villani, Sophia Marie (East Carolina University, 2022)
State-level legislation permitting recreational and medicinal cannabis use continues to be adopted across the United States. California (CA) and Colorado (CO) are two states that have legalized recreational use of cannabis for adults ages 21 years and older and medicinal use for individuals who have a physician’s recommendation. Similar to alcohol and nicotine products, efforts to prevent cannabis use and associated risks are needed for youth and young adults under 21 years of age. Social host ordinances (SHOs) are public policies that hold noncommercial property owners or tenants responsible for hosting or allowing underage drinking on property they own or lease. SHOs are a potential policy that can be implemented or expanded by municipalities to address cannabis use among persons under 21 years of age. The overall purpose of this study is to examine the extent to which cannabis provisions have been incorporated into new or existing city-level SHOs in CA and CO. A systematic protocol was utilized to identify adoption of SHOs in a census of cities and towns in CA and CO. To identify whether a location has a SHO, city and town codes were identified using MuniPro, a municipal law research tool, or a Google search. All identified SHOs were downloaded for data extraction. We documented: (1) presence of a SHO in each city/town; (2) whether alcohol, cannabis, or other substance use was included in the SHO; and (3) type of penalty associated with SHO violation. There were 753 cities/towns identified in CA (n=482) and CO (n=271). Of the 690 cities/towns with a published code, 24% (n=165) had a SHO. All SHOs addressed alcohol use and 31.5% (n=52) of SHOs included cannabis or other substances. Across all SHOs, 52.1% had a hybrid liability structure (civil followed by criminal for repeat offenses), 41.8% used civil-only, and 4.2% used criminal-only. The findings from this study indicate that some communities in states where cannabis is legal have incorporated cannabis and other substances into SHOs in efforts to prevent youth cannabis use. Future research should assess equitable policy adoption and effectiveness of these policies.
Keywords: cannabis; social host ordinance, policy